PENGEMBANGAN MATERI MINAT BERWIRAUSAHA BAGI SISWA KELAS X SMA - Reza Puspita Sari; Elni Yakub; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The high level of unemployment and the growing number of educated unemployed in Indonesia are caused by lack of jobs and interest in entrepreneurship. In this case the school has a greater opportunity in the growing interest in entrepreneurship, especially for students in school. So far, school has not appeared attempts to handleit. Therefore,need to develop a material of interest in entrepreneurship are expected to be used by the teacher guidance and counseling to be teached to students. This material is prepared using methods of research and development (R & D). The purpose of this research is 1) Establishment of material interest in entrepreneurship in terms of clarity, systematics, image support, freshness and completeness of the materials and support games / video 2) To determine the quality of material produced. This material is validated by the supervisor 1 & 2, teachers of Guidance and Counseling and 35 students of class X.1 SMAN 4 Pekanbaru. This material is tested to the students with the allocation of a 3-hour lessons (3 x 45 '). This material consists sense interest in entrepreneurship, the characteristics of entrepreneurs, profit entrepreneurship, factors - factors that affect interest in entrepreneurship, the types of entrepreneurship for students, measures start an entrepreneurial revolution is the attitude of being an entrepreneur, an effort to foster interest in entrepreneurship and inspirational stories of successful entrepreneurs Indonesia. The results of the development of this material indicates the quality of the material produced in the category